2012
DOI: 10.1111/j.1365-2966.2011.20254.x
|View full text |Cite
|
Sign up to set email alerts
|

Radio continuum observations of Class I protostellar discs in Taurus: constraining the greybody tail at centimetre wavelengths★

Abstract: We present deep 1.8 cm (16 GHz) radio continuum imaging of seven young stellar objects in the Taurus molecular cloud. These objects have previously been extensively studied in the submm to near-infrared range and their spectral energy distributions modelled to provide reliable physical and geometrical parameters. We use these new data to constrain the properties of the long-wavelength tail of the greybody spectrum, which is expected to be dominated by emission from large dust grains in the protostellar disc. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…This is in agreement with Pech et al (2016), who show for a smaller sample of protostars consistent fluxes between Class 0 and Class I. However, other sample-limited studies suggest that the radio emission mechanisms could be different for Class 0 and Class I protostars (AMI Consortium: Scaife et al 2011). Spearman's rank correlation coefficient and probability of no correlation is shown in the top-right corner.…”
Section: Flux Densities From Protostarssupporting
confidence: 91%
“…This is in agreement with Pech et al (2016), who show for a smaller sample of protostars consistent fluxes between Class 0 and Class I. However, other sample-limited studies suggest that the radio emission mechanisms could be different for Class 0 and Class I protostars (AMI Consortium: Scaife et al 2011). Spearman's rank correlation coefficient and probability of no correlation is shown in the top-right corner.…”
Section: Flux Densities From Protostarssupporting
confidence: 91%
“…The millimeter measurements using interferometry toward L43, which show the compact feature, suggest dust growth in the vicinity of the central star (< 500 AU). Recent observations have also revealed that SEDs of Class 0 and Class I sources show such small β values (Kwon et al 2009;Scaife et al 2012). Our result supports dust growth at an early stage of star formation.…”
Section: Discussionsupporting
confidence: 86%
“…It is important to disentangle these two emission mechanisms simultaneously as it has been shown that considering freefree and thermal dust components separately can give vastly different values for the spectral slope and normalisation of each component (e.g. Scaife et al 2012). This can have implications when determining physical parameters from the free-free spectra (such as gas mass and electron density) and the thermal dust spectra (such as disc mass and grain size).…”
Section: Spectral Energy Distributionsmentioning
confidence: 99%
“…Extended soft (< 1 keV) X-ray emission has been detected from the DG Tau jet out to 5 arcsec coincident with the optical outflow, and both hard (> 1 keV) and soft emission has been observed from the source (Güdel et al 2008). In the radio, DG Tau has been shown to have a compact and elongated morphology close to the source in the direction of the optical outflow and possesses a spectral index typical of free-free emission at frequencies between 5-20 GHz (Cohen et al 1982;Cohen & Bieging 1986;Rodríguez et al 2012;Scaife et al 2012;Lynch et al 2013;Ainsworth et al 2013).…”
Section: Dg Taumentioning
confidence: 99%